Substrate Preference and Population Structure of Lingulid Shell Species on the North Coast of East Java - Rakmawati Rakmawati; Sucipto Hariyanto; Bambang Irawan; Fatmawati Patang; Supanut Pairohakul (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
Lingulid shell (Brachiopoda: Lingulata) is a marine invertebrate that still exists. The mangrove profile on the north coast of East Java shows the potential to become a habitat for lingulid shell. Despite the significant potential, the lack of similar previous data on substrate profiles, population, and species distribution in East Java shows that the presence of lingulid shells has received less attention, suggesting the need for conservative efforts to conserve and sustainable uses of marine resource. Therefore, this study aimed to describe the habitat ecology of lingulid shell on the north coast of East Java based on regency or city, population structure, internal distribution pattern, and substrate profile, as well as identify species distribution. In addition, confirm the lingulid shell species by molecular identification based on cytochrome oxidase subunit I (COI) gene. Sampling was carried out using the purposive sampling method by digging the substrate in the plot area to a depth of 5-10 cm on the north coast of East Java to obtain lingulid frame substrate which was tested based on the fraction (size).  The results showed that lingulid shell could be found in Surabaya City as well as other regencies including Pasuruan, Probolinggo, Situbondo, Bangkalan, Pamekasan, and Sumenep. The discovery results identified the Lingula anatina species based on morphological and molecular characteristics. The population density of lingulid shell in East Java was found to be 52.6 individuals.m-2, while the internal distribution had no continuity. Furthermore, the presence and distribution of Lingula anatina had a preference for silt substrates.